DOI: 10.3990/1.9789036536356
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and computational study of srain sensitivity in superconducting Nb3Sn

Abstract: This work is the result of efforts by many people, both in a professional and a personal sense. During my time in Berkeley I had the opportunity to work with friendly and supportive people who were pushing back scientific boundaries, regarding the limits of superconducting high field technology. It is an odd but good experience to read papers from various authors detailing one scientific breakthrough or another, and then to meet them in person. Being a multi-cultural hub, Berkeley also allowed me to meet and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 121 publications
(276 reference statements)
2
7
1
Order By: Relevance
“…Although the experimental strain range is limited, two trends can be distinguished: the off-stoichiometric thin films have a similar strain sensitivity to the wires, which is in-line with their random [110]-[100] in-plane crystal orientation, and the off-stoichiometric A15 compositions that also determine the critical properties in wires. For the stoichiometric thin film and bulk samples a reduced strain sensitivity is observed, which is in-line with our observations that when approaching stoichiometry, the sensitivity to strain rapidly reduces (see figure 2.24 in [36]). The reason for this reduced sensitivity, however, should not be sought in crystal alignment, but in the presence of the spontaneous tetragonal distortion, which affects the way that externally applied strain enters the lattice structure.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Although the experimental strain range is limited, two trends can be distinguished: the off-stoichiometric thin films have a similar strain sensitivity to the wires, which is in-line with their random [110]-[100] in-plane crystal orientation, and the off-stoichiometric A15 compositions that also determine the critical properties in wires. For the stoichiometric thin film and bulk samples a reduced strain sensitivity is observed, which is in-line with our observations that when approaching stoichiometry, the sensitivity to strain rapidly reduces (see figure 2.24 in [36]). The reason for this reduced sensitivity, however, should not be sought in crystal alignment, but in the presence of the spontaneous tetragonal distortion, which affects the way that externally applied strain enters the lattice structure.…”
Section: Resultssupporting
confidence: 91%
“…These findings are in contrast to other analyses in which mostly an a priori assumption was made that changes in the phonon spectrum [28,[45][46][47][48][49], or changes in the electron DOS [50][51][52], are the dominant cause for the large strain sensitivity of Nb 3 Sn. We also note that an assumption that changes in the phonon spectrum dominate the effects of strain, is in conflict with the experimental evidence that ρ n changes substantially with strain [33,36]: ρ n is at temperatures below 18K mainly determined by defect scattering and not by the phonons.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…Ten Haken et al [121] picked up on this idea and showed that the key factor in this description is the deviatoric strain component dev . Meanwhile, this type of scaling description has been refined by further experimental observations [216,217] and the role of deviatoric strain has been understood a-priori in terms of the disruption that it causes in the crystal structure and hence in the electronic density of states [181,[218][219][220].…”
Section: Mechanical Nb 3 Sn Cable Modelling 321 Introductionmentioning
confidence: 99%